Comparative technical efficiency of differentgillnet fishing sectors of Kerala - Thomas, Saly N; Hridayanathan, C (Indian Journal of Fisheries, 2011)
Based on the level of technology adopted and species targeted, four sub-sectorswere identified within the gill net sector viz., non motorised small mesh,motorised small mesh, motorized large mesh and mechanised large mesh sectors.The technical and economic efficiency of operation of these four sub-sectors wereanalyzed. The technical efficiency with reference to fishing effort and productivityindicated that there is a direct relationship in terms of fishing effort with thelevel of technology but no such direct relationship was observed in terms ofproductivity.IntroductionBetter technologies obviously have abetter access to fishery resources; butthese generally involve higher cost. Thetechno-economic efficiency of differentfishing systems is an important factor inthe allocation of scarce resources such ascapital. The sustainable development offishing through the co-existence ofdifferent sectors needs basic informationon their comparative efficiency.Â Thecomparative technical and economicperformance of different fishing systemsin different parts of the world have beenreported (Librero et al., 1985; Panayotouet al., 1985; Tokrishna et al., 1985;Fredericks and Nair, 1985; Khaled, 1985and Jayantha and Amarasinghe, 1998).The gill net fishing being a lowenergy fishing technique is favoured inrecent years in the context of alarming